Mr - O'Donnell, James (My University, 2017)
I will present a multistate demographic approach for analysing the longitudinal dynamics of housing and homelessness. The approach is applied to a sample of highly disadvantaged individuals in Australia who are thought to be experiencing, at risk of or vulnerable to homelessness to assess how well private housing markets and interpersonal support networks provide stable and secure housing trajectories vis-à-vis public and community (social) housing. This is particularly important given declining investment in public housing in recent decades and the greater emphasis placed on private rental markets and interpersonal support networks in housing vulnerable populations. A multi-level survival model is specified to estimate the hazards of exiting a current accommodation episode to one of five different housing and homeless states. Model outputs are applied to a multistate life table model to estimate the duration of episodes and the incidence and duration of subsequent episodes of homelessness. The results suggest that housing trajectories within this population are highly volatile particularly for those outside social housing. Private housing markets carry an increased risk of housing exit with the homes of family and friends being the most common destination. The housing support of family and friends, in turn, is very prevalent and important among this population but is usually time limited and often precipitates multiple and repeated episodes staying with family and friends as well as more severe forms of homelessness. These findings warrant policy consideration as to how housing markets can provide better affordability and security for low income households.
Keywords: Housing -- Equity (including use of); Housing -- Conditions; Housing -- Government assistance; Housing, communities and neighbourhoods; Housing; Government assistance; Conditions; Equity (including use of); Housing, community and neighbourhoods